Condylar Position Changes and Prognosis in Patients with Unilateral Mandibular Condylar Fracture Treated Non-surgically - 임지혜 (The Graduate School, Ajou University, 2024)
목적 : 하악 과두 골절의 치료 방법을 선택하는 데 있어 다양한 방법의 선택이 가능하다. 이 연구의 목적은 하악 과두 골절 환자에서 나이와 골절 위치에 따라 삼차원적인 위치 변화를 파악하고 예후와의 관련성을 평가하기 위함이다._x000D_ 재료 및 방법 : 본 연구는 후향적 연구로써 2005년부터 2023년까지 아주대학교 치과병원에서 편측성 하악 과두 골절로 진단받아 비수술적 처치를 받은 환자 40명을 대상으로 하였다. 골절 시 컴퓨터 단층영상(CT)을 촬영하였고 비수술적 처치를 받은 후 6개월 이상 경과된 시점에서 평가하였다. 삼차원에서 시간에 따른 하악 과두 좌표의 이동량을 측정하였고 골 리모델링 시 임상 검사 결과를 통한 예후를 파악하였다. 통계적 분석을 위해 paired t-test, independent t-test, Pearson’s correlation analysis를 시행하였다. _x000D_ 결과 : 골절 시 이환 측 하악 과두의 변위는 통계적으로 유의미하게 차이가 났다. (Paired t-test, P<0.05). 골 리모델링 시 회복량은 전후 측을 제외한 상하 측과 내외 측에서 나이와 음의 상관관계를 보였다 (Pearson’s correlation analysis, P<0.05). 골절 위치에 따라 관절낭내와 관절낭외에서 유의미한 위치 회복량 차이가 있었다 (Independent t-test, P<0.05)._x000D_ 결론 : 하악 과두는 골절 시 전내하방으로 이동하였고 비수술적 처치 후 19세 이하의 나이에서 통계적으로 유의미한 양이 회복되었다. 관절낭내 골절보다 관절낭외 골절에서 회복량이 컸다. 모든 연령층에서 기능적 예후는 양호했다. 하악 과두 골절에서 비수술적 처치는 선택가능한 치료법이다.|Objectives: A variety of treatment options are possible for a mandibular condylar fracture including non-surgical treatment. The purpose of this study is to identify three-dimensional changes of the condylar positions in patients treated non-surgically according to patients’ age and location of fracture, and to evaluate its relationship with prognosis._x000D_ Materials and Methods: This study, designed retrospectively, includes 40 patients with unilateral mandibular condyle fracture treated non-surgically at Ajou University Dental Hospital from 2005 to 2023. Computed tomography was taken at the time of fracture, and evaluated at the time of more than six months after non-surgical treatment. The amount of movement of the highest point of condyle head was measured in three dimensions. After at least 6 months of bone remodeling, the prognosis was evaluated with clinical examination on mouth opening limitation, malocclusion, deviation on opening, temporomandibular joint disorder, and facial asymmetry. Paired t-test, independent t-test, and Pearson’s correlation analysis were used for statistical analysis._x000D_ Results: Difference of position was statistically significant on the affected side at the time of fracture and after more than six month later (Paired t-test, P<0.05). The amount of positional recovery to the superior and lateral direction showed a statistically significant negative correlation with age (Pearson’s correlation analysis, P<0.05). There was a statistically significant difference in the amount of position recovery between intracapsular and extracapsular fracture (Independent t-test, P<0.05). _x000D_ Conclusion: After non-surgical treatment, the condylar head of fractured mandible was statistically significantly recovered laterally and superiorly under 19-year-old age group. The amount of recovery was greater in extracapsular fracture group than the amount in intracapsular fracture group. Functional prognosis was good in all age groups. Non-surgical treatment can be a favorable treatment option in pediatric and adolescent patients.
학위논문(석사)--임상치의학과,2024. 8
Keywords: CT; bone remodeling; displacement; mandibular condylar fracture; non-surgical treatment; prognosis